Collaborative Project Based Blended Learning on Resilience and Student Learning Outcomes - Sulastri, Indrayani Ari; I Made Tegeh; Ketut Agustini (Universitas Pendidikan Ganesha, 2023)
The COVID-19 pandemic is indirectly causing rapid and dramatic changes in the learning process, one of which is the need to hold lectures online with subsequent implications for student wellbeing. The main problem of conducting this research is the ineffectiveness of the learning process during the Covid-19 pandemic so that to restore their resilience and learning outcomes was an important things to be focused on. The aims of this study were 1) to analyze the significant differences in resilience and the English learning outcomes simultaneously between students who studied collaborative project based blended learning with direct blended learning, 2) to analyze differences in resilience between students who studied collaborative project based blended learning with direct blended learning, 3) analyzing differences in the learning outcomes between students who learn with collaborative project based blended learning and direct blended learning. This research is a quasi-experimental study with posttest only control group design. The population of this study was eleven class from grade IX of Junior high school. Resilience data was collected by questionnaire, learning outcomes data was collected by multiple choice tests. Data were analyzed descriptively and analyzed by using multivariate analysis of variance at a significance level of 5%. The results showed, there were differences in resilience and English learning outcomes with better results for students who studied with the collaborative project based blended learning model. Based on this, collaborative project based blended learning model can be effectively used to improve resilience and learning outcomes of student in junior high school.